Upaya Mempercepat Kematangan Buah Kopi Arabika dengan Aplikasi Hormon - Silalahi, Edo Hasiholan; Astuti, Yohana Theresia Maria; Kautsar, Valensi (Program Studi Agroteknologi INSTIPER, 2024)
Coffee is a plantation crop with significant economic value, commonly processed into flavorful beverages. Arabica coffee farmers generally face challenges during harvest and post-harvest, particularly with the necessity to pick ripe, red berries. However, during harvest, farmers often do not selectively pick the cherries, resulting in the collection of not only red but also yellowish or green berries. Plant growth regulators (PGRs) are synthetic chemicals that mimic the role of endogenous hormones. This study aims to investigate the interaction between different hormone types and varieties on the ripening of Arabica coffee berries, assess the impact of various hormones on berry maturity, and evaluate the effect of different varieties on the ripening process. The research utilized a completely randomized design (CRD) with two factors: plant growth regulators (PGRs) and coffee varieties. The observed parameters included the number of fruiting nodes per tree, the number of fruits per node, the number of red fruits in the first harvest, the number of red fruits in each subsequent harvest (across three stages), and the weight of green beans per 100 seeds. The analysis revealed no significant interaction between the application of different types of growth regulators (PGRs) and coffee varieties in accelerating the maturation of Arabica coffee berries. Notably, the Yellow Catura variety treated with the growth regulator Ethrel showed a better effect in accelerating berry maturity.